Argentine pearl fish : A complete study of the Argentine pearl fish, Cynolebias bellottii - Boschi, Enrique E. (1957)
Etymology Cynolebias: Lebias: with dog-like teeth; bellottii: in honor of Dr. Bellotti, who obtained the species. Taxonomy Class: Teleostomi Order: Cyprinodontiformes Sub-Order: Cyprinodontidei Family: Cyprinodontidae Genus: Cynolebias Steindachner Species: Cynolebias bellottii Steindachner